Duties Of Insurance Intermediaries: Confronting The Issues - Chew, Nurjaanah Abdullah Li Hua (Journal of Malaysian and Comparative Law, 2003)
This article will present briefly the legal relationship of an insurance intermediary with his/her principal. An understanding of this legal relationship will put into perspective many issues that are faced by both parties. The duties that are owed by one party to the other depend on this very basis. Thus, the remedies available when there is a breach of such duties are also similarly affected.